2013
DOI: 10.1186/1471-2229-13-221
|View full text |Cite
|
Sign up to set email alerts
|

Global RNA sequencing reveals that genotype-dependent allele-specific expression contributes to differential expression in rice F1 hybrids

Abstract: BackgroundExtensive studies on heterosis in plants using transcriptome analysis have identified differentially expressed genes (DEGs) in F1 hybrids. However, it is not clear why yield in heterozygotes is superior to that of the homozygous parents or how DEGs are produced. Global allele-specific expression analysis in hybrid rice has the potential to answer these questions.ResultsWe report a genome-wide allele-specific expression analysis using RNA-sequencing technology of 3,637–3,824 genes from three rice F1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 51 publications
3
50
0
Order By: Relevance
“…On the other hand, high-throughput gene-expression profiling in heterotic cross combinations has been carried out in both maize and rice, and a large number of genes have been found to be differentially expressed in the hybrids and their parents (17); some of these genes were reported to display nonadditive expression, in support of over-dominance, but others were mainly additive, supporting the dominance hypothesis. In addition, allelic variation in gene expression in hybrids has been reported in maize and rice (18). However, very few of the data obtained from high-throughput transcriptome analysis have been integrated with phenotypic profiles or mapped to single genetic loci associated with yield heterosis.…”
mentioning
confidence: 99%
“…On the other hand, high-throughput gene-expression profiling in heterotic cross combinations has been carried out in both maize and rice, and a large number of genes have been found to be differentially expressed in the hybrids and their parents (17); some of these genes were reported to display nonadditive expression, in support of over-dominance, but others were mainly additive, supporting the dominance hypothesis. In addition, allelic variation in gene expression in hybrids has been reported in maize and rice (18). However, very few of the data obtained from high-throughput transcriptome analysis have been integrated with phenotypic profiles or mapped to single genetic loci associated with yield heterosis.…”
mentioning
confidence: 99%
“…Nonadditive gene expression is the result of allelic interactions that modify regulatory networks that lead to gene activity patterns different from average parental values (Stupar and Springer, 2006). Furthermore, unexpected allelic expression patterns were observed in hybrids that deviated from the allelic ratios of their parents (Guo et al, 2004;Stupar and Springer, 2006;Springer and Stupar, 2007;Paschold et al, 2012;Song et al, 2013). Although nonadditive expression patterns and unexpected allelic ratios have been observed in hybrids of different species, none of these expression types have yet been associated with the evolutionary origin of these genes.…”
mentioning
confidence: 99%
“…In the rice hybrid Xieyou9308, 17% of transcripts showed significant allelic bias at the tillering and heading stages [56]. A similar study of a reciprocal F1 hybrid between rice Nipponbare and 93–11 revealed that 22.7% of genes exhibited significant allelic expression differences [57]. In Arabidopsis , about 40% of genes showed allelic expression differences in the hybrid [58].…”
Section: Discussionmentioning
confidence: 99%